The enhancement of self-directedness in the studies of English books for specific purposes: an analysis of ESP study books - Kildė, Laura (Journal of Education Culture and Society, 2022)
Aim. It has been acknowledged by research that self-directedness proves to be fundamental in learning processes. Despite the fact that self-directedness is vital in the perspective of lifelong learning, there is an insufficient amount of known research that focuses on enhancing self-directedness in the studies of English for Specific Purposes (ESP). In order to expand the body of knowledge in this field, the aim of this work is to establish the types of tasks used in ESP study books which contribute to learners’ self-directedness. Methods. The study employs the methods of relevant literature analysis and comparative analysis of three ESP study books published by Oxford University Press, Pearson Education Limited and Macmillan, which are designed for the intermediate and upper-intermediate students of Business English. Results and conclusion. The comparison shows that the analysed ESP study books contribute to the enhancement of self-directedness through a communicative type of tasks (reading, vocabulary building, speaking, listening activities), which correlates with the categories of Remembering, Understanding, Applying, Analysing, Evaluating, and Creating of Bloom’s Revised Taxonomy by Lorin Anderson and David Krathwohl (2001). Thus, the findings allow to conclude that reading, vocabulary building, speaking, and listening tasks provided in the three ESP study books are designed to develop not only learners’ linguistic competences, but also their self-directedness. Cognitive value. Understanding the types of tasks that encourage learners to transition from low-order thinking skills to high-order thinking skills, which enables them to self-direct their learning, may be of fundamental importance in the studies of English for Specific Purposes.